Neurocognitive Deficits in Euthymic Bipolar Patients - Aysegul Demirel; Omer Faruk Demirel; Muhammed Tayyib Kadak; Alaattin Duran (Psikiyatride Güncel Yaklaşımlar, 2012)
Neurocognitive deficits detected in bipolar patients have a negative influence on clinical course and severity. We reviewed studies on neurocognitive deficits in euthymic bipolar subjects and their possible neuroanatomical correlates. We also examined studies suggesting deficits seen in euthymic patients may be endophenotypes of the disorder. Results of the studies in euthymic patients and their healthy relatives indicate that have cognitive dysfunctions especially of verbal memory, learning and executive domains, which were found to be related to prefrontal cortex and temporo-limbic circuitry. Longitudinal studies investigating heritability of cognitive impairment in bipolar disorder and its relation with brain connectivity and epigenetic mechanisms are needed.